Highlights from Faraday Discussion: Designing New Heterogeneous Catalysts, London, UK, April 2016. Issue 54 (16th June 2016) - Fischer, Nico; Manyar, Haresh G.; Roldan, Alberto
Abstract : The Faraday Discussion on the design of new heterogeneous catalysts took place from 4–6 April 2016 in London, United Kingdom. Abstract : The Faraday Discussion on the design of new heterogeneous catalysts took place from 4–6 April 2016 in London, United Kingdom. It brought together world leading scientists actively involved in the synthesis, characterisation, modelling and testing of solid catalysts, attracting more than one hundred delegates from a broad spectrum of backgrounds and experience levels – academic and industrial researchers, experimentalists and theoreticians, and students. The meeting was a reflection of how big of an impact the ability to control and design catalysts with specific properties for particular processes can potentially have on the chemical industry, environment, economy and society as a whole. In the following, we give an overview of the topics covered during this meeting and briefly highlight the content of each presentation.